Obesity among type 2 diabetes mellitus at Sidama Region, Southern Ethiopia - Bizuayehu, Temesgen; Menjetta, Tadesse; Mohammed, Metsihet (PLOS ONE, 2022)
Background Type 2 diabetes is becoming highly prevalent worldwide and it is one of the leading causes of mortality. The cause of mortality among these patients is mostly related to the dominant presence of modifiable cardiovascular risk factors such as obesity. The aim of the current study is therefore to determine the prevalence of obesity and its associated factors among patients with type 2 diabetes mellitus at Sidama region, Ethiopia. Method Institution-based cross-sectional study design was implemented to determine the prevalence of obesity and its associated factor among patients with type two diabetes at Hawassa University Comprehensive Specialized Hospital and Yirgalem General Hospital from October 16 2018 to December 21, 2018. A simple random sampling technique was implemented to select 314 study participants. After obtaining consent, different patients’ related data were collected using a questionnaire. Patients’ records were also reviewed. 4ml of the blood sample was collected from each study participant and analyzed for lipid profile test. Blood glucose level was done using COBAS INTEGRA 6000. A binary logistic regression was used to assess factors that have an association with obesity. A P-value of <0.05 was considered statistically significant. Result The majority of the study participants (67.2%) were male and 61.8% of the study participants were aged >45years. The overall prevalence of overweight and obesity among the study participants was 36.3% and 18.8% respectively. About 41% of the study participants have a normal BMI. Females were more obese (28.2% Vs 14.2%) than males and BMI stratification by sex was statistically significant (P = 0.02). Sex (AOR = 3.0, CI = 1.6–5.7, P-Value = 0.001) and TG (AOR = 3.6, CI = 1.6–8.3, P-Value = 0.003) are factors that were independently associated with obesity among type 2 DM patients. Conclusion Overweight and obesity among type two diabetic patients were prevalent. In addition, obesity and overweight disorder are common among T2DM and gender and triglycerides levels were associated with obesity.